2007
DOI: 10.1017/s1479262107835659
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity within Lablab purpureus and the application of gene-specific markers from a range of legume species

Abstract: Molecular markers have been used to study genetic diversity within a set of Lablab purpureus accessions collected from the southern states of India. Amplified fragment length polymorphism (AFLP) molecular marker studies using a total of 78 L. purpureus accessions with nine primer combinations showed there was very little genetic diversity within the L. purpureus accessions from the southern Indian germplasm collection as compared to a set of 15 accessions from other international germplasm collections that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
1
24
2
Order By: Relevance
“…The average gene diversity was as low as 0.32 at SSR marker locus, KTD 250 and as high as 0.72 at SSR marker locus KTD 241 with an average of 0.52 among 16 genotypes. The average gene diversity in the present study is more than that reported in dolichos bean by Venkatesha et al, (2007) and (Kinmani et al, 2012), by Sarikamis et al, (2009) in common bean and by Gwag et al, (2006) in mung bean.…”
Section: Ssr Marker-based Genetic Diversitycontrasting
confidence: 51%
“…The average gene diversity was as low as 0.32 at SSR marker locus, KTD 250 and as high as 0.72 at SSR marker locus KTD 241 with an average of 0.52 among 16 genotypes. The average gene diversity in the present study is more than that reported in dolichos bean by Venkatesha et al, (2007) and (Kinmani et al, 2012), by Sarikamis et al, (2009) in common bean and by Gwag et al, (2006) in mung bean.…”
Section: Ssr Marker-based Genetic Diversitycontrasting
confidence: 51%
“…The low diversity within the Kenyan L. purpureus accessions was also displayed in the principal coordinate analysis (PCoA) plot (Figure 2) with a tight cluster of points. A PCoA plot for L. purpureus accessions from UAS Bangalore and from Southern states of India also revealed a tight cluster of points [12]. The diversity however was increased by including accessions from Africa indicating greater genetic diversity across the continents.…”
Section: Discussionmentioning
confidence: 92%
“…Different marker systems have been used to identify genetic diversity in Lablab purpureus. These include simple sequence repeats [10,11], gene specific primers and expressed sequence tags (EST) [12]; Random Amplified Polymorphic DNA (RAPDs) [13][14][15][16] and Amplified fragment length polymorphism (AFLP) [12,[17][18][19]. AFLP markers are the choice markers for this study.…”
Section: Introductionmentioning
confidence: 99%
“…In comparable lablab studies using RAPDs and SRRs, Rai et al, (2010) (Wang et al, 2006). The low amplification of this study could be attributed to use of primers that were not specifically designed from lablab species, therefore primer sequence did not coincide with axon/intron regions from the genome (Venkatesha et al, 2007).…”
Section: Discussionmentioning
confidence: 62%
“…To date, no SSR markers for Lablab purpureus have been reported. However, the vast amount of markers available from related legume species can be applied in lablab studies considering the fact that mapping within the legume species provide evidence that these markers can be used in neglected species such as Lablab purpureus (Venkatesha et al, 2007;Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%